The Effect of Mature Adipocyte-Derived Dedifferentiated Fat (DFAT) Cells on a Dorsal Skin Flap Model. (2nd January 2016) - Kashimura, Tsutomu; Soejima, Kazutaka; Asami, Takashi; Kazama, Tomohiko; Matsumoto, Taro; Nakazawa, Hiroaki
ABSTRACT: Background: Dedifferentiated fat (DFAT) cells, isolated from mature adipose cell, have high proliferative potential and pluripotency. We report on the expansion of flap survival areas on the back of rats administrating DFAT cells. Materials and Methods: Intraperitoneal adipose tissue was collected from a male Sprague-Dawley (SD) rat. The mature fat cells were cultured on the ceiling surface of culture flask to isolate DFAT cells. On day 7 of the culture, the flask was inverted to allow normal adherent culture. A dorsal caudal-based random pattern flap measuring 2 × 9 cm was raised on each SD rat. We prepared a control group ( n = 10) and a flap base injection group in which DFAT cells were injected 2 cm from the flap base ( n = 10) and a flap center DFAT injection group ( n = 10). In which DFAT cells at 1 × 106 cells/0.1 ml were injected beneath the skin muscle layers of the flap. The flap survival areas were assessed on day 14 after surgery. Results: The mean flap survival rates of the control group, flap center injection group and flap base injection group were 53.6 ± 6.1%, 50.6 ± 6.4% and 65.8 ± 2.4%, respectively. The flap survival areas significantly expanded in the flap base injection group ( p < .05). In H-E staining beneath the skin muscle layer connective tissue thickened in the flap base injection group. In the India ink staining, abundant neovascularization was observed inside the thickened parts. Conclusion: The injection of DFAT cells into the flap base promoted the expansion of survival areas.